Key performance indicators in rugby sevens: a systematic review - Finnegan, C.; Scriney, M.; Goss, H.; Walsh, J. C.; Bezbradica, M.; O`Hagan, A. D. (International Journal of Sports Science & Coaching, 2025)
Performance analysis serves as a crucial feedback mechanism in sport. Key performance indicators (KPIs) are essential to this, yet research predominantly examines KPIs relative to outcomes. This systematic review synthesises existing literature on KPIs in Rugby Sevens to identify their application, context and classifications while highlighting gaps and inconsistencies in the field. A systematic search across seven electronic databases identified 18 relevant publications meeting inclusion criteria, detailing 220 unique KPIs. These KPIs serve diverse purposes, including assessing winning or losing, team ranking, and scoring or conceding, reflecting the complexity of performance analysis. The majority (56%) of studies focused on game or tournament outcomes, while 33% examined performance. Despite diverse applications, there is a notable focus on outcome-oriented research, potentially limiting holistic effectiveness. Notably, 46% of the studies provided operational definitions for KPIs, leaving a sizeable proportion (54%) without explicit definitions. This review highlights the complexity of the performance analysis domain and KPI usage within Rugby Sevens and advocates for use of an existing framework to standardise definitions. Addressing these gaps will facilitate a more consistent and effective approach to performance analysis, promoting deeper insights into the multifaceted nature of the sport and evolve the overall landscape of Rugby Sevens performance assessment.